The 1996 and 1997 Social Accounting Matrices (SAM) for Vietnam - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
The Vietnam Social Accounting Matrix (SAM), VIETSAM, is constructed for 1996 and 1997, and includes 97 producing sectors with eight agricultural sectors, two agricultural service sectors and 13 food processing industries. In addition, the SAM includes five factors of production (three types of labor distinguished by skill level, one type of capital and one type of land), six household types (distinguished by rural/urban, agricultural/non-agricultural, wage/self-employed), and one account each for enterprises, government, investment/savings and rest-of-world. The rest-of-world account is a purely non-trade-related account that keeps track of financial transfers between Vietnamese institutions and the rest of the world. Imports and exports of goods and services are distinguished by trading partner - more specifically, 94 partner countries are identified.